Saccharum officinarum L. by-products (pith and rind) as potential source of prebiotic in vitro - Abdul Ghani Zidan, Dina (2019)
Agricultural residues are normally present in massive amounts, and their costs of disposal are very high. Notwithstanding their rich nutritional values, the wastes remain under-utilized commercially due to inadequate study. Sugarcane (Saccharum officinarum L.) by-products; rind (SR) and pith (SP) promote well-being, probably as natural ingredients for functional and medical food industry. The aims of the research were to evaluate the health benefits and functional properties of Sugarcane by-products (SB) through the estimation of their chemical compositions, antioxidant capacities (DPPH and FRAP assays) and phytochemical compounds (phenolic and flavonoids) as well as to evaluate the prebiotic properties of enzymatically produced xylooligosaccharide (XOS) including; non-digestibility experiment using α-amylase and artificial gastric acid juice and selective fermentation using pure cultures namely: Lactobacillus casei Shirota (LcS), Bifidobacterium animals subsp. Lactis and Escherichia coli. Both SR and SP were found to have high total dietary fiber contents (58.91% to 69.10% DW, respectively), with high proportion of insoluble dietary fiber. The available carbohydrate content (AC) in SR (31.72% ± 0.47 DW) was significantly (p<0.05) higher compared to SP (23.07% ± 0.45 DW). The high content of dietary fiber and available carbohydrate are characteristics that made SB as fermentable potential food. The result of antioxidant activities revealed that SR had significantly higher radical scavenging activity (62 % ± 1.06) than SP (51.32% ± 1.18) using the DPPH assay and higher reducing power activity (6.98 ± 0.30 mg FeSO4/100g DW), than SP (2.77 ± 0.32 mg FeSO4/100g DW) using the FRAP assay. In addition, SB showed high total phenolic contents (SR= 469 ± 3.25; SP= 273 ± 4.27 mg GA/100g), and total flavonoids contents (SR= 269 ± 16.80; SP= 169 ± 4.36 mg QE /100g), being significantly higher in SR (p<0.05). This study showed that SB contained XOS known as prebiotic agent. In the present study, XOS mixture was successfully produced from SR and SP (XOS-SR and XOS-SP) respectively. XOS-SR was composed of 1.78 ± 1.01 and 1.62 ± 0.02 mg/mL xylobiose and xylotriose respectively, while XOS-SP was composed of 1.75 ± 0.05, 1.04 ± 0.06 and 0.19 ± 0.02 mg/mL xylobiose, xylotetrose and xylotriose, respectively. Based on the non-digestibility test, around 84 to 88.24% of XOS consumed would reach the colon and then be utilized by the probiotic as small amounts of the saccharides were hydrolyzed by α-amylase (8.29 to 12.87%) and by gastric juice (3.47 to 4.07%). The fermentation test demonstrated that XOS derived from SB is a potential prebiotic ingredient due to the evidence that probiotic bacteria (LcS and Bifidobacterium) increased significantly (p<0.05), while E. coli growth was suppressed in vitro condition. In addition, the probiotic bacteria supplemented with XOS produced high amount of SCFAs, known as fermentation end products during the fermentation, indicating the ability of tested bacteria to utilize XOS-SR and XOS-SP, where acetic acid was the predominant end product, followed by propionic acid and lactic acid. In conclusion, sugarcane by-products are potential ingredients for development of functional foods.